The Adoption of Innovative Strategies for Enhanced Service Delivery in the South Africa Public Sector - NDUDUZO C NDEBELE; ANDREW ENAIFOGHE (Social Sciences and Education Research Review)
The objective of the study is to examine the challenges and prospects for the adoption of innovative strategies to enhance the delivery of service in the South African public sector. The public sector is under pressure to provide new public services with increasingly scarce resources. In the context of South Africa, public service is essential because public services are promised and guaranteed by the constitution, and more citizens depend on state provisions, due to the high unemployment rate in the country. As such, using a qualitative approach this study intends to interrogate the concept of innovation in the public sector and its role in ensuring that the public sector provides enhanced services and can meet the needs of the citizens. This article further provides a systematic review of the empirical literature on barriers and benefits within public sector innovation processes and suggests ways in which public service employees can overcome these barriers. The study concludes that public sector innovation has a considerable and varied impact on public sector performance as a result there's a need for innovation to be an integrated part of public sector service delivery.